ARTIN EXPONENT OF u(4,ZP)USING BRAUER COEFFICIENT THEOREM - Majeed, Awss Jabbar (Al-Nahrain Journal of Science, 2010)
In this paper, we consider the Artin exponent of the Groups of unitriangular matrices U(n,F) from the principal character of its cyclic subgroups and denoted by A(U(n,F)) WHERE n=4 and F=ZPp is prime number, and we found that A(U(4,ZP)) =p8Furthermore, we found that, the order of this group / U(4,ZP)/ =p4 its exponent exp (U(4,ZP))=p and found general forms of all conjugacy classes